2002
DOI: 10.1038/nn827
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary action and conscious awareness

Abstract: Humans have the conscious experience of 'free will': we feel we can generate our actions, and thus affect our environment. Here we used the perceived time of intentional actions and of their sensory consequences as a means to study consciousness of action. These perceived times were attracted together in conscious awareness, so that subjects perceived voluntary movements as occurring later and their sensory consequences as occurring earlier than they actually did. Comparable involuntary movements caused by mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

94
1,515
8
12

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 1,296 publications
(1,629 citation statements)
references
References 13 publications
94
1,515
8
12
Order By: Relevance
“…This is what we would expect based on early studies on binding which showed that longer actionoutcome intervals were associated with reduced binding (Haggard et al, 2002). This work implied that the binding effect is restricted to sensorimotor timescales.…”
Section: Main Textsupporting
confidence: 72%
See 3 more Smart Citations
“…This is what we would expect based on early studies on binding which showed that longer actionoutcome intervals were associated with reduced binding (Haggard et al, 2002). This work implied that the binding effect is restricted to sensorimotor timescales.…”
Section: Main Textsupporting
confidence: 72%
“…First, they replicate the basic binding effect, and confirm that temporal contiguity is an important factor (cf. Haggard, et al, 2002). Second, their study again demonstrates effects of action on time perception, using a task that does not rely on the much-criticised 'Libet clock' method of reporting event times (see also, Engbert et al, 2008;Moore et al, 2009, for …”
Section: Main Textmentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast to predictions one could derive from the above discussed research, Demanet et al found that greater effort increased temporal binding, therefore implying a stronger implicit sense of agency under conditions of high task-unrelated physical effort. These findings were attributed to the notion that effortful actions boost the interoceptive sensory-motor information of willed effort, which may act as a cue to self-agency (Haggard et al, 2002;Lafargue & Franck, 2009;Vierkant, 2014).…”
Section: Sense Of Agency and Effortmentioning
confidence: 99%